2011
DOI: 10.1118/1.3521406
|View full text |Cite
|
Sign up to set email alerts
|

Tumor control probability in radiation treatment

Abstract: Patients undergoing radiation therapy (and their physicians alike) are concerned with the probability of cure (long-term recurrence-free survival, meaning the absence of a detectable or symptomatic tumor). This is not what current practice categorizes as "tumor control (TC);" instead, TC is taken to mean the extinction of clonogenic tumor cells at the end of treatment, a sufficient but not necessary condition for cure. In this review, we argue that TC thus defined has significant deficiencies. Most importantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 67 publications
0
57
0
Order By: Relevance
“…Zaider et al, showed that there are numerous important factors that determine tumor response to radiation, such as cell cycling, interaction with the immune system, selection effects, spatial heterogeneity of the tumor and its capillary network, etc. (30) have not been taken into account using LQ-Poisson model. However, the EUD has the advantage of fewer model parameters compared to another TCP or NTCP models, and allows more clinical flexibility.…”
Section: Precaution To Use Tcp In Order To Rank and Optimize Radiothementioning
confidence: 99%
“…Zaider et al, showed that there are numerous important factors that determine tumor response to radiation, such as cell cycling, interaction with the immune system, selection effects, spatial heterogeneity of the tumor and its capillary network, etc. (30) have not been taken into account using LQ-Poisson model. However, the EUD has the advantage of fewer model parameters compared to another TCP or NTCP models, and allows more clinical flexibility.…”
Section: Precaution To Use Tcp In Order To Rank and Optimize Radiothementioning
confidence: 99%
“…Tumor treatment planning, especially in the case of radiotherapy, uses many different stochastic process calculations, relevant on different time scales, from femtoseconds to years, as reviewed in (16)(17)(18)(19) and in the online AAPS Supplement section S.4.1. The influence on IIV of stochastic fluctuations at the single cell level is considered (16,18); an approach similar to the statistical methods of population PK/PD is also used to analyze IIV [reviewed, e.g., in (20)].…”
Section: Pk/pd Modelingmentioning
confidence: 99%
“…The influence on IIV of stochastic fluctuations at the single cell level is considered (16,18); an approach similar to the statistical methods of population PK/PD is also used to analyze IIV [reviewed, e.g., in (20)]. …”
Section: Pk/pd Modelingmentioning
confidence: 99%
“…A number of new localization and fixing techniques, dose calculation algorithms and treatment concepts make radiotherapy even more precise. With deeper understanding of the concepts of factors such as the biologically effective dose (BED), equivalent uniform dose (EUD), α/β, tumor control probability (TCP) and normal tissue complication probability (NTCP), biological responses could be translated into a means for radiation physics optimization (11)(12)(13). To conclude, there is an urgent clinical need for this new radiation model, and its feasibility is based on growing knowledge regarding radiation responses and advances in modern radiation physics and imaging technology.…”
Section: Why Response-modified Radiation Treatment?mentioning
confidence: 99%